Reflections on Best English Teacher Practices in Using Technology for Distance Learning Solutions during the Disruption Period of the Covid-19 Pandemic - Sri Supiah Cahyati; Wahyu Wijayati; Aniati; Sri Haryati; Septyana Prasetianingrum (Indonesian Journal of Education (INJOE), 2022)
This paper discussed the best practice experiences of English teachers in using technology applications during the disruption of the COVID-19. This study also understood teachers' opinions about the reasons that require them to use learning technology. The author's observations on distance learning and semi- structured interviews were methods of obtaining the data. Based on the data analysis and discussion, this paper reveals that the superior practice of teachers using distance learning applications is a professional need for English teachers as the implementation of government policies to close schools and open classes remotely. To meet the demands of student learning, the use of learning applications is part of the learning solution in the era of pandemic disruption. The school's policy is that the best access to learning was by applying learning technology handled professionally. This study also understands that the main factors in the use of learning applications by teachers and students are the use of technology in the digital era to improve competence and learning outcomes in English. The author also understands that the technology learning approach  is  constructive  for  teachers  and  students  with technological pedagogical beliefs. Therefore, these skills must be sustainable to improve teachers' teaching competencies and professionalism as an educational approach to the technocultural approach